Triple Entente or Unholy Alliance? Official Russian Attitudes toward Britain and France, 1906 to 1914. - Tomaszewski, Fiona K. (My University, 1992)
This dissertation is an examination of official Russian attitudes toward Britain and France from 1906 to 1914, from the inauguration of a constitutional regime in Russia to the outbreak of World War One. In order to illustrate the motivations behind Russian foreign policy making at a critical juncture in the history of Russian autocracy, several groups within the Russian government and bureaucracy are examined, including the Emperor and the Court, the Foreign Ministry and the Ministries of Finance and Trade and Commerce.
A wide spectrum of opinions about Russia's Entente partners existed among Russia's rulers. Although ideological apprehensions about partnership with the two western bourgeois constitutional states did bother some officials, (Russian officialdom overwhelmingly accepted this unusual partnership as a matter of necessity. The policy of the Triple Entente -- to preserve the status quo in Europe and to contain Germany -- was accompanied by Stolypin's domestic reform programme, all in an attempt to save the 'ancien regime' in Russia. But, as with the domestic reforms, Nicholas II's foreign policy lacked the imagination necessary to halt the precipitous decline of autocratic power in Russia.
The severe constraints on Russian power that had resulted from the Russo-Japanese War and the 1905 revolution shaped Russia's dependent relationship with Britain and France. As Russia recovered from the twin disasters of 1905, she began to place more demands on Britain and France and to reassert herself in the international arena. As the international situation became more tense, official Russia became more adamantly committed to the Triple Entente. The thesis illustrates and analyzes at close range how the alliance system in Europe immediately prior to World War One became increasingly rigid and how, as a result, it became one of the major factors in the outbreak of general war.
Keywords: History; History